2021
DOI: 10.1109/access.2021.3066457
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Trustworthiness for the Internet of Things

Abstract: IoT systems use sensors to collect data from smart environments and manage resources through data analysis. An IoT system deals with many connected devices with different network and hardware constraints in a real-world scenario. An IoT system needs to handle low-latency data analysis, security threats, internal vulnerabilities, and network disconnections, which cause data loss and incorrect decisions. Trustworthiness (also known as dependability) provides various features for an IoT end-to-end data flow, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 146 publications
(238 reference statements)
0
13
0
Order By: Relevance
“…[13] Smart irrigation Wireless sensor network, sensor node, and irrigation [8] Pest control For pest monitoring, IoT and deep learning with global and local features are used. [12] Leaf area index synthetic aperture radar (SAR) images Air Quality Monitoring [46] Detecting Water contamination IoT and machine learning [48] Monitoring Water quality IoT with smart sensors [30] Investigation of Water contamination Big data and SVM [27] Lagoon water Machine learning and image analysis [30] Water quality Neural network [24] Indoor air quality IoT, LoRaWAN [7] Intelligent air quality system UV light, AI and sensors [16] Air quality characterization Heterogeneous sensors, AI [25] Air pollution Gas sensors [4] CO2 monitoring IoT and cloud technologies…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Smart irrigation Wireless sensor network, sensor node, and irrigation [8] Pest control For pest monitoring, IoT and deep learning with global and local features are used. [12] Leaf area index synthetic aperture radar (SAR) images Air Quality Monitoring [46] Detecting Water contamination IoT and machine learning [48] Monitoring Water quality IoT with smart sensors [30] Investigation of Water contamination Big data and SVM [27] Lagoon water Machine learning and image analysis [30] Water quality Neural network [24] Indoor air quality IoT, LoRaWAN [7] Intelligent air quality system UV light, AI and sensors [16] Air quality characterization Heterogeneous sensors, AI [25] Air pollution Gas sensors [4] CO2 monitoring IoT and cloud technologies…”
Section: Literature Reviewmentioning
confidence: 99%
“…The advancement of IoT technology in agriculture operations has enabled the use of sensors at every stage of the agricultural process, such as how much time and resources a seed requires to mature into a completely grown crop. Every object that can be operated over the internet is referred to as a device [4]. Wearable IoWT (Internet of Wearable Things) gadgets like smart watches and home management solutions like Google Home have made IoT devices very popular in consumer markets [5].…”
Section: Introductionmentioning
confidence: 99%
“…Wireless sensor networks, smart grids, and some IoT devices are examples of CPSs [47]. Even though there is no consensus in the literature to define the trustworthiness property and its scope [48], we can define a CPS's trustworthiness, in general terms, as the property of behaving as expected under adversarial conditions [47]. Network malfunction, Byzantine errors, and faulty nodes are examples of adverse conditions that can affect a system's trustworthiness.…”
Section: Trustworthiness In Cyber Physical Systemsmentioning
confidence: 99%
“…Network malfunction, Byzantine errors, and faulty nodes are examples of adverse conditions that can affect a system's trustworthiness. Some authors limit this definition to system security issues only [49], while others propose a broader scope and relate trustworthiness with other terms such as resilience, availability, reliability, scalability, maintainability, heterogeneity, data quality, hardware resources, and fault management policies [48]. We can find many approaches to measuring or providing trustworthiness in literature, referring to different elements.…”
Section: Trustworthiness In Cyber Physical Systemsmentioning
confidence: 99%
“…The original concept of dependability can be briefly described as the capability of a system to provide users with trusted, reasonable, reliable, and correct services, or, in other words, the ability to ensure continuous and uninterrupted provision of critical services. 19 In Junior and Kamienski, 20 it is attributed by the authors that the two terms Dependability and Trustworthiness refer to the same concept that explains that the trustworthiness of IoT systems is largely determined by their ability to adapt and respond to what vulnerability flaws are present during their operational cycles. Based on a brief review of the current state of research, it can be concluded that the term Dependability is often restricted to the study of security performance in dealing with malicious network attacks under IoV scenarios.…”
Section: Introductionmentioning
confidence: 99%